Probing the molecular interactions in some promising biofuel blends (prenol, 1-hexanol, 1-octanol, and 1-decanol): volumetric, acoustic, and transport approach - Ankush Bakshi; Chandani Sharma; Amit Kumar Sharma; Meena Sharma (Chemical Thermodynamics and Thermal Analysis)
The reported work involves measuring various thermo-physical properties such as density (ρ), speed of sound (u), viscosity (η), and refractive index (nD) of some pure potential/promising biofuels (prenol, 1-hexanol, 1-octanol, and 1-decanol) and blends of prenol with these over the entire range of mole fraction from temperature T = (298.15 to 323.15) K and at 0.1MPa pressure making use of an Anton Paar vibrating U-tube density and sound velocity meter (DSA 5000 M) and Abbemat refractometer respectively. The collected thermo-physical data has been employed to compute various deviational and excess properties such as isentropic compressibility (κs), deviation in isentropic compressibility (Δκs), deviation in refractive index (ΔnD), deviation in viscosity (Δη), excess molar volume (VmE), and excess Gibb's free energy of activation of viscous flow (ΔG*E). Correlation of all the excess and deviational properties with composition has been made with the help of the Redlich-Kister type polynomial equation and standard deviation has been ascertained. Moreover, the temperature and composition dependence of these properties has also been analysed. The present work has been taken up for analysing the nature of interactions and structural effects prevalent between these blends and the collected thermo-physical data can be employed in the fields of designing and developing bio-based diesel fuels.